Cost-Consequences of Cladribine Tablets for the Treatment of Highly Active Relapsing–Remitting Multiple Sclerosis in Italy - Barbara Polistena; Anna Maria Provenzano; Caterina Rizzi; Elena Colombo; Roberto Bergamaschi (Neurology and Therapy)
Abstract Introduction Multiple sclerosis (MS) is a chronic autoimmune disease impacting the central nervous system. Individuals with highly active relapsing–remitting MS (HA-RRMS) frequently experience symptomatic episodes lasting more than 24 h, followed by a remission period completely or partially symptom free. This study aimed to assess the economic impact of cladribine tablets for the treatment of patients with HA-RRMS in the Italian context. Methods A Markov model developed by PRECISIONheor for simulating treatment outcomes in patients with HA-RRMS aged over 18 years over three treatment lines was adapted to the Italian National Health System organization. The model considers direct costs of treatment and relapse management, as well as costs related to adverse events and indirect costs. The model adopts the societal perspective and a 4-year time horizon. Uncertainty was addressed through deterministic sensitivity analysis. Results The analysis considered 16,691 out of 55,635 Italian patients with HA-RRMS (30%). Treatment with cladribine tablets extended the duration of patients’ responsive stage (relapse free) from 1.3 months (worst scenario) to 1.4 months (best scenario) when compared to oral disease-modifying therapies (DMTs) and from 2.4 to 5.7 months when compared to monoclonal antibody DMTs. cladribine tablets were associated with cost savings ranging from 69.9% to 10.9% compared to oral DMTs and from 74.3% to 33.0% compared to monoclonal antibody DMTs. The cost savings per additional month in responsive stage ranged from € 27,663.2 to € 4154.3 vs oral DMTs and from € 16,224.5 to € 3035.3 vs monoclonal antibody DMTs. Conclusion Cladribine tablets are associated with a benefit in terms of prolonging the non-relapsing phase in patients with HA-RRMS, as well as substantial direct cost savings in comparison with all other DMTs. Our analysis suggests that adopting cladribine tablets for HA-RRMS enables clinical benefits over a 4-year time horizon and savings for Italian society.